Fishing for Fetal Alcohol Spectrum Disorders: Zebrafish as a Model for Ethanol Teratogenesis - Lovely, Charles Ben (Zebrafish, 2016)
Fetal Alcohol Spectrum Disorders (FASD) describes a wide array of ethanol-induced developmental defects, including craniofacial dysmorphology and cognitive impairments. It affects ∼1 in 100 children born in the United States each year. Due to the pleiotropic effects of ethanol, animal models have proven critical in characterizing the mechanisms of ethanol teratogenesis. In this review, we focus on the utility of zebrafish in characterizing ethanol-induced developmental defects. A growing number of laboratories have focused on using zebrafish to examine ethanol-induced defects in craniofacial, cardiac, ocular, and neural development, as well as cognitive and behavioral impairments. Growing evidence supports that genetic predisposition plays a role in these ethanol-induced defects, yet little is understood about these gene–ethanol interactions. With a high degree of genetic amenability, zebrafish is at the forefront of identifying and characterizing the gene–ethanol interactions that underlie FASD. Because of the conservation of gene function between zebrafish and humans, these studies will directly translate to studies of candidate genes in human populations and allow for better diagnosis and treatment of FASD.